Back Cover: Nickel‐Catalyzed Reductive Amidation of Unactivated Alkyl Bromides (Angew. Chem. Int. Ed. 37/2016). Issue 37 (28th July 2016) - Serrano, Eloisa; Martin, Ruben
Abstract : The mighty dragon, representing a nickel catalyst, combines the starting materials (isocyanates and unactivated alkyl bromides) with his claws to afford the final aliphatic amide products in his fire breath, as described by R. Martin and E. Serrano in their Communication onpage 11207 ff. The versatile reaction proceeds under mild conditions and has excellent chemoselectivity. The catalytic cycle and the regeneration of the Ni catalyst in the course of the cycle are represented by the ouroboros‐like image, itself a symbol of cyclicality.